2003
DOI: 10.1113/jphysiol.2003.044313
|View full text |Cite
|
Sign up to set email alerts
|

Effects on the right motor hand‐area excitability produced by low‐frequency rTMS over human contralateral homologous cortex

Abstract: Repetitive transcranial magnetic stimulation (rTMS) has long lasting effects on cortical excitability at the site of stimulation, on interconnected sites at a distance and on the connections between them. In the present experiments we have used the technique of transcallosal inhibition between the motor cortices to examine all three effects in the same protocol. Ten healthy subjects received 900 rTMS stimuli at 1 Hz from a figure of eight coil over the left motor hand area. The intensity of rTMS was above the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
110
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(132 citation statements)
references
References 35 publications
(55 reference statements)
18
110
2
2
Order By: Relevance
“…These results are in agreement with previous studies showing that, at a larger size of a test MEP, the magnitude of IHI is decreased (Ferbert et al, 1992;Daskalakis et al, 2002). We observed no differences in the magnitude of IHI between test MEP2 and test MEP3, and this is also in agreement with previous results (Gilio et al, 2003).…”
Section: Sicisupporting
confidence: 94%
“…These results are in agreement with previous studies showing that, at a larger size of a test MEP, the magnitude of IHI is decreased (Ferbert et al, 1992;Daskalakis et al, 2002). We observed no differences in the magnitude of IHI between test MEP2 and test MEP3, and this is also in agreement with previous results (Gilio et al, 2003).…”
Section: Sicisupporting
confidence: 94%
“…The steep slope of the SICIcurve in musicians may allow more effective control of enhanced plasticity and benefit performance. This might be not the case in focal dystonia, because some studies have described reduced SICI at rest (Ridding et al, 1995;Gilio et al, 2003), although this finding is inconsistent (Stinear and Byblow, 2004a,b;Butefisch et al, 2005;Rosenkranz et al, 2005).…”
Section: Beneficial Versus Maladaptive?mentioning
confidence: 99%
“…Altogether, these findings raised the hypothesis that reduction of excitability in the intact hemisphere may contribute to improvements of motor function in stroke (Hummel and Cohen, 2006). Accordingly, previous studies in healthy volunteers showed that downregulation of excitability in one motor cortex, by repetitive TMS (rTMS) on that area, results in an increased excitability of the opposite motor cortex and an improved motor performance of the ipsilateral hand (Gilio et al, 2003;Kobayashi et al, 2004;Avanzino et al, 2008). Here, to directly investigate cortical modifications induced by an abnormal asymmetric use of the two limbs, we propose an experimental approach based on short-term hand immobilization in healthy volunteers.…”
Section: Introductionmentioning
confidence: 95%